The repaired durophagous scar in the shell of a lingulid brachiopod immediately after the end Ordovician mass extinction. Issue 2 (2nd April 2020) - Huang, Bing; Li, Rongyu
Abstract: Repaired shell injuries, widely reported mainly on mollusks, give first hand evidence of biological activity in fossil communities. Scars in fossil brachiopods from predation are rarely found, particularly after major biotic crises. A repair scar on a lingulid brachiopod Pseudolingula ? sp. that lived immediately after the end Ordovician mass extinction is reported for the first time here. The specimen, cohabited with other components of Cathaysiorthis fauna, was collected from the basal Shiyang Formation (earliest Rhuddanian, Llandovery, Silurian), Jiangxi, southeast China. The scar's near-margin position and its drape-like shape, together with the quiet middle to deeper shelf living environment and nearly infaunal lifestyle of the species, suggest that the shell damage was biotic-induced, from a failed predation, possibly by a nautiloid cephalopod. The successful repair supports previous studies showing that environmental conditions ameliorated quickly after the extinction. To analyze its repair mode, another repaired specimen of its living relative Lingula anatina collected from the Yellow Sea, China was examined here as well. Compared to the much more efficient repair for the living lingulids, the drape-like structure of the scar on the shell of Pseudolingula ? sp. is more similar to the published repair specimens of Cambrian lingulate brachiopods, which may indicate the evolution of its repair mechanisms. Bing Huang [bhuang@nigpas.ac.cn ], State Key Laboratory of Palaeobiology and Stratigraphy, Nanjing Institute of Geology and Palaeontology, Center for Excellence in Life and Paleoenvironment, Chinese Academy of Sciences, 39 East Beijing Road, Nanjing 210008, China; Rongyu Li [lir@brandonu.ca ] Department of Geology, Brandon University, 270-18th Street, Brandon, Manitoba R7A 6A9, Canada.